Pancreatic Islet Cell Amyloidosis Manifesting as a Large Pancreas - Onur, Mehmet Ruhi; Yalniz, Mehmet; Poyraz, Ahmet Kursad; Ozercan, Ibrahim Hanifi; Ozkan, Yusuf (Korean Radiological Soc, 2012)
A 39-year-old female patient presented to our hospital with epigastric pain lasting for two months. Laboratory results showed impaired glucose tolerance. Ultrasonography of the patient showed a hypoechoic, diffusely enlarged pancreas. CT revealed a large pancreas, with multiple calcifications. On MRI, a diffusely enlarged pancreas was seen hypointense on both T1- and T2-weighted images with heterogeneous enhancement after gadolinium administration. A biopsy of the pancreas revealed primary amyloidosis of islet cells. Decreased signal on T1-weighted images without inflammation findings on CT and MRI were clues for the diagnosis.
Keywords: Pancreas; Amyloidosis; Ultrasonography; Computed tomography; Magnetic resonance imaging